Η Τεχνητή Νοημοσύνη ως εργαλείο ή ως συσσυγραφέας; Ακαδημαϊκές και νομικές προκλήσεις - Τρίγκας, Νικόλαος (Παιδαγωγικά ρεύματα στο Αιγαίο, 2025)
Artificial Intelligence (AI) models are increasingly becoming highly sophisticated, but they still remain dependent on the quality of their training data. This paper aims to contribute to the better understanding of the tricky issues surrounding authorship in the era of AI. Now the question arises: how to appropriately acknowledge the use of AI tools and technologies in producing a creative work? The related question should be examined: who can claim copyright protection for an AI-generated (or an AI-assisted) work? This study based on qualitative data indicates that AI cannot be your (co-)author, at least for now, due to its limitations (confirmed by empirical research). The bibliographic review suggests that an author should disclose whether and to what extent she/he used any AI models when producing a scientific work. In the present technological environment, only human beings (and not tools, computers or other machines) can be authors of copyrightable works. Yet works generated by humans using AI are eligible for copyright depending on the circumstances and mainly on the extent to which it was used to create the final work. However, this situation may change in the future if artificial general intelligence (AGI) (human‑level intelligence AI) becomes a reality.